Mixed convection and radiation heat transfer in a horizontal duct with variable wall temperature - Ganesan, R.; Narayanaswamy, Ramesh; Perumal, K. (Taylor and Francis Ltd., 2015)
In this research, experiments are performed to study the laminar flow mixed-convection heat transfer with radiation effects for a hydrodynamically fully developed and thermally developing airflow in a horizontal duct. The duct cross section is made of two differentially heated isothermal vertical walls and two adiabatic horizontal walls with aspect ratios 1 and 0.5. The total heat transfer from the hot wall to the cold wall of the duct depends on the mixed convection and also on the surface radiation heat transfer that takes place within the duct. The analysis of experimental data for the Nusselt number from the hot wall of the duct shows that it is important to consider the effects of surface radiation, and to accounted for them, in the design and analysis of flow and heat transfer through ducts. The flow field within the duct is also made visible by a suitable smoke flow visualization method. The heated air moves upward, accumulates near the top wall adjacent to the hot wall of the duct, and gets circulated continuously to the cold wall on the opposite side. The accumulated flow is thermally stable; the stable conditions can reduce the heat transfer enhancement due to the buoyancy force. The results show that flow condition and surface radiation interaction significantly affect the total Nusselt number and the surface temperature variation along the walls.